Sporadic Creutzfeldt-Jakob Disease: Finding the Needle in the Haystack - Ghazanfar, Auns; Pittford, Alexandra; Fernando, Kryshani (Curēus (Palo Alto, CA), 2024)
Sporadic Creutzfeldt-Jakob disease (SCJD) is a rare neurodegenerative disease with a very low prevalence. The aetiology is theorised to be genetic. Modern laboratory techniques, such as the real-time quaking-induced conversion (RT-QuIC) assay, have allowed us to diagnose CJD with greater sensitivity and specificity. Previously, the diagnosis rested primarily on a post-mortem brain biopsy. Although advancements in laboratory techniques have allowed earlier diagnosis of CJD, the treatment is still supportive. Research is still ongoing for a curative treatment, but so far, the fatality rate remains at 100%. Early vague symptoms of CJD delay the diagnosis further, as multiple pathologies need to be ruled out before consideration of the diagnosis of CJD. This case report describes a similar case of sporadic CJD diagnosed in an otherwise fit and well patient.